Information Fusion for Colorectal Polyps Medical Image Segmentation - Zhou, Zhuo; Duan, Yinghua; Huang, Weilan; Pei, Fengyun; Liu, Bo; Huang, Jun (Archives of Clinical and Biomedical Research, 2022)
Training a deep neural network often requires a large amount of annotated data, which is scarce in the medical image analysis domain. In this work, we present a simple yet effective technique for enhancing medical image segmentation neural network through information fusion. The proposed approach utilizes information from different spatial scales and combines them in a learnable way. Experimental results on two benchmark datasets demonstrate that the proposed fusion module improves the segmentation performance of state-of-the-art neural networks.